ESTABLISHING A BASE POPULATION OF INDIVIDUAL SELECTION FOR LOW MAINTENANCE REQUIREMENTS IN TERM OF DIETARY PROTEIN LEVEL IN THE AFRICAN CATFISH (Clarias gariepinus) - Bambang Iswanto; Rommy Suprapto; Imron Imron (Indonesian Aquaculture Journal, 2019)
The farming industry of the African catfish (Clarias gariepinus) in Indonesia is affected by a high feed cost during the grow-out phase resulting in low economic return. Selective breeding to produce new strains with low maintenance requirements is one of the potential solutions to overcome the problem. The present study aimed to identify and study the performance of the base population of African catfish treated with feed low in dietary protein during the grow-out phase. Out of 100 broodstock pairs, 96 pairs had produced successful hatching. Approximately 1,000 larvae from each pair were reared separately to reach seven-week-old juveniles. Then, 50 individuals from each pair were selected to form the base population. The base population was reared for four months and fed with commercial feed containing 12% crude protein resulting in final mean body weight of 82.04 ± 34.66 g, a specific growth rate of 2.02%/day, a feed conversion ratio of 4.23, and survival rate of 25.15%. At the end of the grow-out phase, the size variation among treated fish was relatively high (variation coefficient of 42.31%). The subsequent individual selection stage had identified that 325 individuals (equal to 26.93% of the total population) had the best performances with a mean body weight of 128.80 ± 22.80 g, selection differential of 46.80 g, and selection intensity of 1.35. These results suggested the potency of the selected base population be used in the forming of the next generation.